2017
DOI: 10.1007/s00429-017-1589-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological variability masks differences in functional neuroanatomical networks and their effectiveness to modulate response inhibition between children and adults

Abstract: Executive functions are well-known to undergo developmental changes from childhood to adulthood. Considerable efforts have been made to elucidate the affected system neurophysiological mechanisms. But while it is well-known that developmental changes affect intra-individual variability, this potential bias has largely been neglected when investigating the neurophysiology underlying developmental differences between children and adults. We hypothesize that due to differences in intra-individual variability of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 67 publications
4
24
0
Order By: Relevance
“…Yet, reliable interactions "condition × group" were obtained after accounting for intra-individual variability in the data using RIDE (Ouyang et al, 2011). Already previous results suggested that differences in intra-individual variability bias comparisons between adolescents and adults when it comes to neurophysiological correlates of cognitive control (Bodmer et al, 2018). It is shown that the interaction "condition × group" was obtained for the S-cluster in the time window of the target-P1 and the C-cluster in the search interval of the target-N2.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Yet, reliable interactions "condition × group" were obtained after accounting for intra-individual variability in the data using RIDE (Ouyang et al, 2011). Already previous results suggested that differences in intra-individual variability bias comparisons between adolescents and adults when it comes to neurophysiological correlates of cognitive control (Bodmer et al, 2018). It is shown that the interaction "condition × group" was obtained for the S-cluster in the time window of the target-P1 and the C-cluster in the search interval of the target-N2.…”
Section: Discussionmentioning
confidence: 87%
“…However, this is an expected finding since it is likely that intra-individual variability in neurophysiological data may preclude the detection of reliable differences between adolescents and adults (Bodmer et al, 2018). The sLORETA analysis was performed because the choice of time and electrodes to quantify the ERP data may have failed to capture the difference.…”
Section: Standard Event-related Potentials (Erps)mentioning
confidence: 98%
See 3 more Smart Citations